Functional properties from nile tilapia (Oreochromis niloticus (Linnaeus, 1758)) frame protein hydrolysis - Prasetyo, Dwi Yanuar Budi; Setyastuti, Aryanti Indah; Kresnasari, Dewi; Apriliani AGS, Dwi (Universitas Malikussaleh, 2021)
This study was to determine the functional properties of fish protein hydrolysis produced from tilapia frame. This study used a factorial design where the first factor was different types of proteolytic enzymes (E1 = bromelain, E2 = papain) and the second factor was different hydrolysis time (T1 = 5 hours, T2 = 6 hours) and was carried out with 3 replications. The results of the analysis showed that the different types of enzymes and hydrolysis time had a significant difference on the yield, degree of hydrolysis, proximate, viscosity, and protein solubility. This product has the potential to be used as food additives that can give special function properties so further research needs to be carried out to investigate these special functional properties for health and reduce the fat content that can affect the self-life product.Keywords: Functional properties; Protein hydrolysis; Nile tilapia frame